Omega-3 Fatty Acids Ameliorate Sleep Deprivation-Induced Histomorphological Alterations in the Rat Prostate - Mahmood, Nomana; Qamar, Abdullah; Anjum, Kaukab; Khan, Muhammad Marghoob; Ali, Humaira; Ali, Ayesha (Journal of Rawalpindi Medical College, 2025)
Objective: The primary objective of this study was to observe the impact of chronic sleep deprivation on the histomorphological features of the rat prostate gland and to evaluate the potential protective effects of omega-3 fatty acid supplementation. Materials & Methods: Thirty male Sprague-Dawley rats (200-300g) were randomly divided into three groups (n=10 per group): Group A (control, maintained on a normal sleep-wake cycle), Group B (sleep deprivation, subjected to 16 hours of sleep deprivation followed by an 8-hour sleep opportunity daily for 60 days), and Group C (sleep deprivation + omega-3, subjected to the same sleep deprivation regimen as Group B, supplemented with 260 mg/kg/day omega-3 fatty acid via oral gavage). Post-euthanasia and after dissection, prostate tissues were processed for histological observation using H&E and Masson’s trichrome staining to assess epithelial apoptosis, collagen deposition, and smooth muscle architecture. Statistical analyses were performed using SPSS software version 21, with p<0.05 considered statistically significant. Results: Group A (control) showed normal histological structure. Group B (sleep deprivation) exhibited a significantly higher frequency of epithelial apoptosis (p<0.05), increased interacting collagen deposition (p<0.001), and marked irregularities in the smooth muscle layer surrounding the acini (p=0.002). Group C (sleep deprivation + omega-3) demonstrated reduced epithelial apoptosis, collagen deposition, and smooth muscle distortion relative to Group B. Conclusion: The present study observed that sleep deprivation caused significant changes in the histomorphology of the rat prostate gland, including epithelial apoptosis, collagen fibre deposition in the interacting space, and irregular arrangement of the smooth muscle fibres around the acini. Additionally, omega-3 fatty acid supplementation had an ameliorative effect on these histomorphological alterations induced by sleep deprivation.